Episodic therapy for genital herpes in sub-saharan Africa: a pooled analysis from three randomized controlled trials. - Helen A Weiss; Gabriela Paz Bailey; Sam Phiri; Gerard Gresenguet; Jerome LeGoff; Jacques Pepin; David A Lewis; Laurent Belec; Irving F Hoffman; William C Miller; Philippe Mayaud (PLoS ONE)
Background A randomized controlled trial in South Africa found a beneficial effect of acyclovir on genital ulcer healing, but no effect was seen in trials in Ghana, Central African Republic and Malawi. The aim of this paper is to assess whether the variation in impact of acyclovir on ulcer healing in these trials can be explained by differences in the characteristics of the study populations. Methodology/principal findings Pooled data were analysed to estimate the impact of acyclovir on the proportion of ulcers healed seven days after randomisation by HIV/CD4 status, ulcer aetiology, size and duration before presentation; and impact on lesional HIV-1. Risk ratios (RR) were estimated using Poisson regression with robust standard errors. Of 1478 patients with genital ulcer, most (63%) had herpetic ulcers (16% first episode HSV-2 ulcers), and a further 3% chancroid, 2% syphilis, 0.7% lymphogranuloma venereum and 31% undetermined aetiology. Over half (58%) of patients were HIV-1 seropositive. The median duration of symptoms before presentation was 6 days. Patients on acyclovir were more likely to have a healed ulcer on day 7 (63% vs 57%, RR = 1.08, 95% CI 0.98-1.18), shorter time to healing (p = 0.04) and less lesional HIV-1 RNA (p = 0.03). Small ulcers (<50 mm(2)), HSV-2 ulcers, first episode HSV-2 ulcers, and ulcers in HIV-1 seropositive individuals responded best but the better effectiveness in South Africa was not explained by differences in these factors. Conclusions/significance There may be slight benefit in adding acyclovir to syndromic management in settings where most ulcers are genital herpes. The stronger effect among HIV-1 infected individuals suggests that acyclovir may be beneficial for GUD/HIV-1 co-infected patients. The high prevalence in this population highlights that genital ulceration in patients with unknown HIV status provides a potential entry point for provider-initiated HIV testing.